"Self-revolutions of everyday life": the politics of ATG. Issue 2 (3rd July 2021) - Alekseyeva, Julia
ABSTRACT: In 1968, Japan's own "season of politics" was full of strikes, protests, and university closures. Much of the exigence behind students' revolutionary fervor revolved around a "self-revolution in everydayness, " as activists sought to criticize capitalist consumerism and imperialism, and aimed to transform their own depoliticized consciousness. The films of the Art Theater Guild (ATG) reflect these desires. This paper argues that the films produced by ATG are a deeply political film cycle united by a "house style" which serves to destabilize and dehabituate our perception, and echoes the student protesters in their desire for a self-revolution of everyday life.